Inhibitors of α‐amylase and α‐glucosidase: Potential linkage for whole cereal foods on prevention of hyperglycemia. Issue 12 (4th November 2020) - Gong, Lingxiao; Feng, Danning; Wang, Tianxi; Ren, Yuqing; Liu, Yingli; Wang, Jing
Abstract: The strategy of reducing carbohydrate digestibility by controlling the activity of two hydrolyzing enzymes (α‐amylase and α‐glucosidase) to control postprandial hyperglycemia is considered as a viable prophylactic treatment of type 2 diabetes mellitus (T2DM). Thus, the consumption of foods rich in hydrolyzing enzyme inhibitors is recommended for diet therapy of diabetes. Whole cereal products have gained increasing interests for plasma glucose‐reducing effects. However, the mechanisms for whole cereal benefits in relation to T2DM are not yet fully understood, but most likely involve bioactive components. Cereal‐derived phenolic compounds, peptides, nonstarch polysaccharides, and lipids have been shown to inhibit α‐amylase and α‐glucosidase activities. These hydrolyzing enzyme inhibitors seem to make whole cereals become nutritional strategies in managing postmeal glucose for T2DM. This review presents an updated overview on the effects provided by cereal‐derived ingredients on carbohydrate digestibility. It suggests that there is some evidence for whole cereal intake to be beneficial in amelioration of T2DM through inhibiting α‐glucosidase and α‐amylase activities. Abstract : The cereal‐derived α‐amylase and/or α‐glucosidase inhibitor could be targeted for developing valuable whole cereal foods in T2DM dietary managements.